Perbandingan Hukum Penanaman Modal dan Investasi Di Indonesia dan Di Tiongkok - Reky Yuliansyah; Trianda Lestari; Syahrando Muhti (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
Indonesia and China are two countries with rapidly developing economies in Southeast Asia. These two countries have great potential to attract foreign investment. However, there are differences in investment and foreign investment regulations in the two countries. This research aims to compare investment and foreign investment laws in Indonesia and China. This research uses normative legal research methods with a comparative approach. Research data was obtained from literature studies, namely laws, government regulations and other related literature. The research results show that there are similarities and differences in foreign investment and investment regulations in Indonesia and China. Similarities include, recognition of the rights of foreign investors; providing incentives for foreign investors; and resolving investment disputes. The differences include the subject of investment, business fields open to foreign investment, investment requirements. From this research, researchers can draw the title, namely Comparison of investment law and foreign investment in Indonesia and China